1994
DOI: 10.1128/jvi.68.4.2142-2150.1994
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of the JE gene encoding the monocyte chemoattractant protein (MCP-1) in cervical carcinoma cells and derived hybrids

Abstract: Malignant human papillomavirus type 18 (HPV18)-positive cervical carcinoma cells can be reverted to a nonmalignant phenotype by generation of somatic cell hybrids with normal human fibroblasts. Although nontumorigenic hybrids, their tumorigenic segregants, and the parental HeLa cells have similar in vitro properties, inoculation only of nontumorigenic cells into nude mice results in a selective suppression of HPV18 transcription which precedes cessation of cellular growth. Our present study, aimed at understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 63 publications
3
38
0
Order By: Relevance
“…18 However, even though MCP-1 expression is induced after infection by a variety of RNA and DNA viruses, MCP-1 expression is suppressed after epithelial cell infection by HPV in vitro. 19 This parallels the situation in vivo, where advancing cervical intraepithelial neoplasia is associated with loss of MCP-1 expression. 20 The mechanisms responsible for HPV-mediated suppression of MCP-1 expression are unclear.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…18 However, even though MCP-1 expression is induced after infection by a variety of RNA and DNA viruses, MCP-1 expression is suppressed after epithelial cell infection by HPV in vitro. 19 This parallels the situation in vivo, where advancing cervical intraepithelial neoplasia is associated with loss of MCP-1 expression. 20 The mechanisms responsible for HPV-mediated suppression of MCP-1 expression are unclear.…”
mentioning
confidence: 62%
“…MCP-1 expression by HeLa cells in our study contradicts earlier reports. 19 Although the lineage history of the HeLa culture we examined may differ from that used in the earlier study, the HPV genome is still present in the cells we tested (data not shown) and their ability to secrete MCP-1 is unexplained. Nonetheless, in primary epithelial cells, the correlation between E6/E7 expression and suppression of MCP-1 is complete.…”
Section: Chemokine Expression In Cervical Carcinoma Cell Linesmentioning
confidence: 80%
“…56 Further evidence comes from nonmalignant cells shown to contain an inhibitory chemokine. Rosl et al 59 documented that macrophage chemoattractant protein 1 (MCP-1), a chemokine derived from activated macrophages, represses HPV E6 ⁄E7 transcription. This finding was supported by a study in which the introduction of the JE (MCP-1) gene into malignant cells resulted in cell growth retardation.…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%
“…Multiple HPV types have been implicated in the promotion of cervical SCC development. The HPV types found in cervical neoplastic cells were classified by Muñoz et al into those associated with low (6, 11, 13, 40, 42-44, 54, 61, 62, 70, 72, 74, 81) and high (16,18,31,33,35,39,45,51,52,56,58,59,68,73,82) risk of progression to malignancy. In addition, the authors concluded that HPV types 26, 53 and 66 should be considered probably carcinogenic due to the extremely small number of affected patients.…”
mentioning
confidence: 99%
“…[11][12][13] The cervical oncogenic process is initiated by persistent infection with high-risk HPV and mediated by the upregulation of HPV E6/E7 oncoproteins. 14,15 As the overexpression of these oncoproteins is associated with increased risk of lesion progression, the detection of E6/E7 oncoprotein activity should be more specific and a better predictor of cervical cancer risk than HPV DNA detection methods that cannot differentiate between persistent and transient infections. [16][17][18][19][20] Detection of E6/E7 oncoproteins activity can be achieved by testing for E6/E7 mRNA transcripts.…”
mentioning
confidence: 99%